2000
DOI: 10.1902/jop.2000.71.8.1236
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Local Delivery of Alendronate in Reducing Alveolar Bone Loss Following Periodontal Surgery in Rats

Abstract: This study implies that topical delivery of alendronate at the time of surgery reduces bone loss in periodontal procedures involving mucoperiosteal flap surgery. The most effective dose is 200 microg for topical delivery at the surgical site and 400 microg for distant sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 22 publications
8
64
0
5
Order By: Relevance
“…Therefore, it is also possible that the addition of BP at high doses (100 and 200 μg) influenced osteoclasts, osteoclast precursors, and osteoblasts, and excessively inhibited bone metabolic turnover. In contrast, new bone increased in the 1 μg BP+DDM group, suggesting that this additive BP dose (1 μg) was close to the dose that reached the defective bone region in the abovementioned studies performed by Binderman et al (150 μg/kg) 9) and Hikita et al (1.0 mg/kg) 10) . The influence may have been limited to slight inhibition of osteoclasts and may have been too small to influence the entire bone metabolism at this dose.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, it is also possible that the addition of BP at high doses (100 and 200 μg) influenced osteoclasts, osteoclast precursors, and osteoblasts, and excessively inhibited bone metabolic turnover. In contrast, new bone increased in the 1 μg BP+DDM group, suggesting that this additive BP dose (1 μg) was close to the dose that reached the defective bone region in the abovementioned studies performed by Binderman et al (150 μg/kg) 9) and Hikita et al (1.0 mg/kg) 10) . The influence may have been limited to slight inhibition of osteoclasts and may have been too small to influence the entire bone metabolism at this dose.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, it has been reported that BP administration near the extraction socket and extraction site and below the maxillary periosteum on the opposite side improved the osteochondral repair ability of the extraction socket [9][10][11] . However, it is unclear whether or not direct BP administration to the defective bone region exhibits a similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Like other bisphosphonates, alendronate sodium is used for the treatment and prevention of Paget's disease, fibrous dysplasia, and osteoporosis, which are characterized by increased bone turnover and resorption 6 . Recent studies investigating the local effects and systemic side effects of alendronate sodium have shown that locally administered alendronate solution is absorbed by the bone at a rate of 20%-30% at the site of administration, where it inhibits bone resorption 7 .…”
mentioning
confidence: 99%
“…It has also been administered locally to prevent bone loss due to periodontitis in animal models [5][6][7][8]. Nevertheless the effect of bisphosphonates on ridge preservation by local application in humans remains poorly investigated.…”
Section: Introductionmentioning
confidence: 99%